Memórias das esquinas: as trajetórias de prostitutas na batalha pelo bairro da Campina, Belém-Pa - SOUSA, Silvia Lilia Silva (Universidade Federal do Pará, 2023)
In this paper i will look at prostitution in the urban context of Belem, specifically in the Campina neighbourhood, central area of the city of Belém / PA, where bohemia and prostitution in the capital predominated between the 19th and 20th centuries. In this district, the famous zone of the meretrício was built in 1921, also known as“quadrilátero do amor”, that was closed in the 1970s by the military government, and remained so throughout that decade. Starting from the studies of urban anthropology in interlocution with gender studies, I propose in this dissertation to understand the relationship between female prostitutes and the Campina neighborhood, taking into account their trajectories, memories and struggles. Thus, I perceive that among the street corners, nightclubs and small hotels, emerge stories that exist in the memories of these women; narratives that allow the reflection of different interpretations regarding the city. Therefore, they reference other forms of exercising sociability and experiencing the city.